History - Greenwood, Anna, 1971- (Emerald Publishing Limited, 2023)
History has been a source of cultural fascination since ancient times, however little attention has been paid to its potential as a positive force for health and wellbeing, at least until now. Presenting the benefits of historical engagement, and practical tips for making the most of it, Anna Greenwood considers the power this discipline has to spur better health outcomes. A ground-breaking work for history buffs and healthcare providers alike, this new instalment in the Arts for Health series by one of the leading scholars in modern health history advocates for history's ability to deepen sympathies, broaden imaginations, and create community beyond the customary restrictions of time and geography.
Includes index.
Keywords: History -- Philosophy.; History -- Study and teaching -- Philosophy.; Medicine and the humanities.; Medical -- Mental Health.; Popular medicine & health.; elektronické knihy; electronic books